Diptoindonesin G antagonizes AR signaling and enhances the efficacy of antiandrogen therapy in prostate cancer. Issue 8 (24th March 2022) - Mao, Fengyi; Kong, Yifan; Liu, Jinghui; Rao, Xiongjian; Li, Chaohao; Donahue, Kristine; Zhang, Yanquan; Jones, Katelyn; Zhang, Qiongsi; Xu, Wei; Liu, Xiaoqi
Abstract: Background: The androgen receptor (AR) signaling pathway has been well demonstrated to play a crucial role in the development, progression, and drug resistance of prostate cancer. Although the current anti‐androgen therapy could significantly benefit prostate cancer patients initially, the efficacy of the single drug usually lasts for a relatively short period, as drug resistance quickly emerges. Methods: We have performed an unbiased bioinformatics analysis using the RNA‐seq results in 22Rv1 cells to identify the cell response toward Dip G treatment. The RNA‐seq results were validated by qRT‐PCR. Protein levels were detected by western blot or staining. Cell viability was measured by Aquabluer and colony formation assay. Results: Here, we identified that Diptoindonesin G (Dip G), a natural extracted compound, could promote the proteasome degradation of AR and polo‐like kinase 1 (PLK1) through modulating the activation of CHIP E3 ligase. Administration of Dip G has shown a profound efficiency in the suppression of AR and PLK1, not only in androgen‐dependent LNCaP cells but also in castration‐resistant and enzalutamide‐resistant cells in a CHIP‐dependent manner. Through co‐targeting the AR signaling, Dip G robustly improved the efficacy of HSP90 inhibitors and enzalutamide in both human prostate cancer cells and in vivo xenograft mouse model. Conclusions: Our results revealed that Dip G‐mediated AR degradation would be a promising and valuable therapeutic strategy in the clinic.